BORON AND ITS INFLUENCE ON CORROSION STABILITY OF CAST PRODUCTS - N. F. Nevar; U. N. Fasevich; N. V. Lobanovskaya (Литьë и металлургия, 2012)
The purpose of this work is development and research of cast boron materials and technology of their production, intended for work in corrosion environments.